Development of a web service of vehicle inspection in central credit risk - Santos López, Félix Melchor (2011)
The central credit risk companies in Peru collect much information from different external sources and they offer various services to the others enterprises, entities and citizens. Therefore, their information systems are updated constantly. In the world there are many different technologies developed in different language programming, thus it was considered a pain in the neck for software engineers. Fortunately, nowadays there is a framework called Web Service that allows communication, interoperability and exchange among different language programming. The “Vehicle Inspection” system gives all the information about vehicles registered in the country. In addition, this system was developed in J2EE (Java Second Enterprise Edition) and UML (Unified Modeling Language) because are reliable and free technologies; also JMeter is a good test tool that helps to establish the accurate measure of the parameters for a good system performance. As a result, 5 000 concurrent users should not exceed the capacity of this web service.